"Delirium of interpretation": Surrealism, the possessions, and Beckett's outsider artists. Issue 1 (2nd January 2019) - Mooney, Sinéad
ABSTRACT: Samuel Beckett, then a largely unknown member of the Joyce circle, translated a selection of texts for a surrealist special issue of the Parisian journal This Quarter in 1932. Among them were three excerpts from André Breton and Paul Éluard's L'Immaculée Conception in which the authors, using automatism, simulated the verbal styles of various forms of mental illness. This essay argues that, despite an ambivalent attitude to surrealism as a movement, these translations are a key source for Beckett's interest in the irrational and in verbal deviance, and are in fact precursors to the anomalous, self-engrossed "outsider artists" of Beckett's mature work.